Nerve compression as an essential factor in causing ischaemic and post-ischaemic paraesthesiae - Eros Abrantes Erhart (Arquivos de Neuro-Psiquiatria, 1950)
In order to explain why ischaemia produced by compression at the proximal part of the forearm or at the wrist, does not cause sensory disturbances identical to those observed in compression at the upper arm, several experiments were made on ourselves and other subjects. The method used was essentially that of Lewis and Pochin. Circulation was blocked at different levels of the limb by applying the pressure of 200 mm/Hg with a sphygmomanometer cuff; compression of the median, ulnar and tibial nerve trunks was made with the aid of a small cushion under the cuff. We observed always that the nerve compression is an essential factor in causing ischaemic and post-ischaemic paraesthesiae.